Gap Analysis and The Potential of Local Wisdom Jambi as Science Learning Resources - Jufrida Jufrida; Fibrika Rahmat Basuki; Anta Xena; Pretty Pasminingsih (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2019)
This study aims to analyze the gaps and potential of Jambi local wisdom as a basis for the development of science textbooks. This research was a qualitative descriptive study. The research subjects were students of class VIIIE and VIIIF at SMPN 1 Muaro Jambi, which totaled 43 people and science teachers. This study uses the instruments to observations sheet and questionnaires for students and teachers. Data were analyzed descriptively. The results show that; (1) the science textbooks available at SMPN 1 Muaro Jambi not yet have integrated into Jambi local wisdom and there are no questions about scientific literacy; (2) the results of observations indicate that the supporting facilities in science learning such as laboratories are still lacking, but other facilities such as classrooms and library are quite good; (3) material that can be integrated with Jambi local wisdom including substance pressure, vibrations, waves, sound and optical.